Extremely high interleukin-6 blood levels and outcome in the critically ill are associated with tumor necrosis factor- and interleukin-1-related gene polymorphisms - Watanabe, Eizo; Hirasawa, Hiroyuki; Oda, Shigeto; Matsuda, Kenichi; Hatano, Masahiko; Tokuhisa, Takeshi (Critical care medicine, 2005)
To determine the allelic frequencies of interleukin (IL)-6-, IL-1-, and tumor necrosis factor-alpha (TNF)-related gene polymorphisms in critically ill patients with extremely high IL-6 blood level and to examine the genetic effects on their clinical courses. Population-based association study. A general intensive care unit in a university teaching hospital. A total of 150 consecutive critically ill patients recruited at admission to the intensive care unit, regardless of diagnosis, and 150 healthy volunteers. IL-6 blood levels were measured daily with chemiluminescence immunoassay. The IL-6 peak levels were significantly correlated with simultaneously measured TNF (r = .659, p < .0001) and IL-1beta levels (r = .518, p < .0001), respectively. Single nucleotide polymorphism at position -174 and -596 sites of the IL-6 (IL6-174*G/C and IL6-596*G/A), -308 site of the TNF (TNF-308*G/A), and -511 site of the IL-1beta (IL1B-511*C/T) were identified with real-time polymerase chain reaction assay using specific fluorescence-labeled probe. Within the IL-1 receptor antagonist intron 2, a various number of tandem repeat polymorphisms (IL1RN*1-5) were identified after polymerase chain reaction with gel electrophoresis. Allelic frequencies of patients with IL-6 peak levels of > or =10,000 pg/mL (group A) were compared with those of patients with IL-6 peak levels of <10,000 pg/mL (group B). Neither IL6-174*C nor IL6-596*A were recognized in all the subjects; however, group A showed a higher frequency of TNF-308*A (p = .054), IL1B-511*T (p = .013), and non-IL1RN*1 (p = .008) allele compared with group B. TNF-308*A, IL1RN*2 or IL1RN*3 allele carriers of group A showed sustained high IL-6 levels, despite countermeasures against hypercytokinemia, and their survival rate was lower than that of the noncarriers of those high-risk alleles (p = .025). TNF-308*A, IL1RN*2, and IL1RN*3 alleles were associated with the prevalence of the extremely high IL-6 blood level in the critically ill, their uncontrollable blood IL-6 kinetics, and outcome.